2020
DOI: 10.1111/jftr.12384
|View full text |Cite
|
Sign up to set email alerts
|

A Goal‐Theoretic Framework for Parental Screen‐Time Monitoring Behavior

Abstract: Children's screen time (i.e., time spent using computers, televisions, mobile devices) has rapidly increased with the development of mobile technology, and this increase has become a matter of serious concern for teachers, parents, family life educators, psychologists, and other health professionals. High usage rates (more than 2 hours per day) have been associated with low-quality sleep, language acquisition difficulties, and attentional problems in young children. Results of experimental trials to limit scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In their meta-analysis on effective strategies for reducing children's screen time, Jones et al [54] concluded that behavioral interventions tailored to individual needs appear to be particularly effective [54]. This coincides with others who have suggested that other family activities, the context and purpose of use within the family system, and barriers to screen time reduction must be considered [59,60]. Peláez et al [58] also found in their exploration of a 24-hour screen-free challenge that parents directly expressed a need for alternative activities to engage in instead of screen use for them to be successful.…”
Section: Introductionmentioning
confidence: 75%
“…In their meta-analysis on effective strategies for reducing children's screen time, Jones et al [54] concluded that behavioral interventions tailored to individual needs appear to be particularly effective [54]. This coincides with others who have suggested that other family activities, the context and purpose of use within the family system, and barriers to screen time reduction must be considered [59,60]. Peláez et al [58] also found in their exploration of a 24-hour screen-free challenge that parents directly expressed a need for alternative activities to engage in instead of screen use for them to be successful.…”
Section: Introductionmentioning
confidence: 75%
“…For example, Ma et al (2022) found that parental engagement positively predicted children’s social competence, whereas children’s screen time negatively predicted their social competence [ 107 ]. Therefore, parents need to be trained to scaffold and support their young children, to build independence, agency, and empowerment by actively talking about engagement with digital technology [ 25 ] so that young children can be given enough knowledge about how to balance their digital usage and form healthy habits to improve their digital well-being [ 54 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other promising intervention strategies that have been associated with better outcomes for young children include focusing on changing parenting perceptions, substituting screen time with other behaviours, and parental modelling (Lewis et al, 2021). Focusing on shared family goal setting regarding screen use within a self-regulatory framework (Owenz & Fowers, 2020) may be one way to assist families to engage in healthier screen use practices.…”
Section: Interventions To Change Young Children's Screen Use Practicesmentioning
confidence: 99%